Performansi Mesin Pendingin Tipe Chiller untuk Cold Storage dan Indoor Menggunakan Ethylene Glycol Coolant - Azridjal Aziz; Hendrik Syahputra; Rahman Putra Mainil; Afdhal Kurniawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2015)
AbstractRefrigeration device is used to reduce the temperature of the room or cooled material by absorbing heatfrom the room/material. The most refrigeration device operated by using the vapor compression refrigerationcycle. This research was done experimentally using refrigeration device chiller type to cool the ethylene glycolcoolant in the refrigeration box (evaporator unit), and ethylene glycol coolant is used to absorb heat in coldstorage and indoor (test room). The results show for the circulation of ethylene glycol coolant to the coldstorage COP value is 2.80, while the circulation of ethylene glycol coolant to the indoor COP value is 5.12. Onthe testing of ethylene glycol coolant was circulated to the indoor with 1000 Watt cooling load, the COP value is5.19, and for circulated to the cold storage and indoor simultaneously COP is of 3.66. The performance ofchiller refrigeration device is influenced by the cooling load, the greater of cooling load that would affect thework of the compressor so that the pressure in compressor increase and the energy consumption to operate thecompressor also increasing too.Keywords: refrigeration, heat, COP, PF, cooling load.